Egg Production Performance and Prediction of Standard Limits for Traits of Economic Importance in Broiler Breeders - Ali, Murad; Farooq, M.; Durrani, F.R.; Chand, N.; Sarbiland, K.; Riaz, A. (International Journal of Poultry Science, 2003)
The present study was conducted on broiler breeders maintained in 24 different farms located in Mansehra and Abbotabad to investigate egg production performance and develop standard limits for production traits of economic importance. Average number of day-old chicks received at a broiler breeder farm was 19076.29, out of which 16449.08 birds attained sexual maturity and were housed in laying houses. Total hens housed represented 14037.32 females and 1559.70 males (a male to female ratio of 1:9). Reserved male stock (852.06 birds) was 5.18% of the total population. Average mortality during 323.46 days of growth and production period was 13.77%, representing 2.97, 4.99 and 5.81% mortality during brooding, growing and laying periods, respectively. Average age at point-of-lay, age at peak-of-lay and egg laying period were 164.67, 232.83 and 155.46 days. Age at point-of-lay (r = 0.227) and age at peak-of-lay (r = 0.333) were found positively but non-significantly correlated with total mortality in a flock. On the other hand flock size was found negatively correlated with age at point (r = -0.052) and age at peak-of lay (r = -0.415; p<0.04). Egg laying period was found negatively but non-significantly correlated with flock size (r = -0.147) and positively correlated with total mortality in a flock (r = 0.255). Egg laying period was found positively and significantly (P<0.027) associated with percent lay (b = 5.770). Average peak percent lay and percent lay was 83.09 and 59.67%, respectively. Percent lay was found non-significantly and positively correlated with flock size (r=0.184) and mortality ( = 0.085). Similar findings were observed for peak percent lay. Percent lay was found positively and significantly (P<0.033) associated with peak percent lay (b = 0.625). Peak percent lay was found negatively associated with age at peak of lay (b = -0.324; P<0.001) and positively associated with age at point of lay (b = 0.891; P<0.001). Average hen-day and hen-housed egg production was 103.32 and 95.10 eggs, respectively. Hen-day (r = -0.067) and hen-housed egg production (r = -0.074) was found negatively and non-significantly correlated with flock size. Hen-day egg production was found positively associated with peak percent lay (b = 1.600; P<0.035) and egg laying period (b = 0.627; P<0.001). Percent lay, peak percent lay, egg laying period and hen-day and hen-housed egg production was lower than that reported in the literature. Standard limits for minimum number of hens to be housed, maximum level of mortality, maximum age at point of lay, maximum age at peak of lay, minimum peak percent lay, minimum percent lay, egg laying period in response to percent lay and egg laying period in response to hen-day production were 4172.21 birds, 13.11%, 164.36 days, 35.33 weeks, 79.99%, 67.64%, 28.06 weeks and 65.54 weeks, respectively. The standard limits mentioned for various traits shall be maintained in order to make broiler farming more productive.